FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN SISWA DALAM MENGIKUTI PROGRAM KURSUS BAHASA INGGRIS - Ismaliyah, Ismaliyah (Jurnal Manajemen Ekonomi dan Bisnis, 2022)
Education is a conscious effort to prepare students through guidance or training activities for their roles in the future. Every educational institution knows that the learning process in schools will never be static, but always dynamic. Informal education business is a profitable business because it has a long period of time. Therefore, many businesses related to education have emerged, one of which is English courses, this is because English is a universal language. The high interest in taking English courses on the market makes competition between English language course institutions increasingly tight. Currently, we can find many English language educational institutions in various big cities in Indonesia. This research was conducted as part of an English course at the Victory Medan Education Center. This research aims to analyze the factors that influence purchasing decisions for English language learning programs at the Victory Medan Education Center.The data used is primary data taken from 40 Victory Center Medan students. Data processing in this research uses multivariate linear regression analysis. The research results show that partial changes in brand image, location and service quality have a significant influence on selection decisions. At the same time, it is proven that the variables of brand image, location and service quality have a significant influence on selection decisions.